2019
DOI: 10.33549/physiolres.934322
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Diet Containing n-3 Polyunsaturated Fatty Acids and Silymarin on Metabolic Syndrome in Rats

Abstract: The risk of development of metabolic syndrome can be increased by hypertriglyceridemia. A search for effective therapy is a subject of considerable attention. Therefore, our hypothesis is that the fish oil (containing polyunsaturated fatty acids; n-3 PUFA) in a combination with silymarin can more effectively protect against hypertriglyceridemia-induced metabolic disturbances. The study was conducted using a unique non-obese strain of rats with hereditary hypertriglyceridemia an accepted model of metabolic synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
7
1
1
Order By: Relevance
“…Moreover, the combination of silymarin and n-3 fatty acid supplementation may enhance the antihyperlipidemic effect in rats with metabolic syndrome [36]. These discrepancies with our results are probably due to the fact that different breeds and animals with induced liver disorders were used, rather than the healthy animals in our study (EXP1).…”
Section: Discussioncontrasting
confidence: 78%
“…Moreover, the combination of silymarin and n-3 fatty acid supplementation may enhance the antihyperlipidemic effect in rats with metabolic syndrome [36]. These discrepancies with our results are probably due to the fact that different breeds and animals with induced liver disorders were used, rather than the healthy animals in our study (EXP1).…”
Section: Discussioncontrasting
confidence: 78%
“…However, increased gene expression of the Abcg8 transporter indicated higher cholesterol secretion from hepatocytes into bile. ABCG5/8 transporters not only play an important role in sterol absorption and excretion but also provide an important pathway for cholesterol elimination [ 32 , 33 ]. While transcriptional factor SREBF1 is involved in fatty acid synthesis, SREBF2 regulates genes affecting cholesterol metabolism, the most important being HMGCR and the LDL receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia has been evaluated as an important factor in the formation of MetS, and was found to be significantly related to development of MetS, insulin resistance and a marker of chronic inflammation 21,22 . Many studies have shown that n‐3PUFAs in salmon phospholipids could effectively reduce TG levels in mice induced by HF diet to protect against hypertriglyceridemia 23‐25 . However, we found that the levels of TG and DG were significantly increased in the SA4 group versus HF group mice.…”
Section: Discussionmentioning
confidence: 63%